Male Involvement and Prevention of Mother-to-Child Transmission of HIV in Sub-Saharan Africa: An Integrative Review - Auvinen, Jaana; Kylma, Jari; Suominen, Tarja (Current HIV Research, 2013)
Purpose: The purpose of the study was to describe male involvement in programmes for preventing mother-tochild transmission (PMTCT) in Sub-Saharan Africa. The study questions guiding this review were: how are male partners involved in PMTCT programmes in Sub-Saharan Africa and what are the strategies for improvement of male involvement? Methods: An integrative review was conducted based on the data retrieved from the PubMed MEDLINE database. In all, 18 articles were included in this review. Qualitative content analysis was used as a method of data synthesis. Findings: Based on the findings of this review, some studies suggested that men had positive attitudes towards PMTCT programmes. However, also barriers to male involvement were identified. These barriers included negative attitude, lack of resources, fear of human immunodeficiency virus (HIV) test result, marital difficulties, problems with health care services and cultural barriers. Accepting HIV testing was associated with factors related to both wife and husband. Strategies for improving male involvement included ones that focus on men’s and their wives’ resources (sensitizing men about antenatal care (ANC) and PMTCT, focusing on the conjugal context and couples counselling), the development of health care services (tailoring the services to male needs, taking care of health care staff’s resources, developing health care strategies) and the community (educating the community, testing, safer infant feeding). Implications: We should highlight the male participation in PMTCT programmes. However, more research is needed in order to evaluate their impact on PMTCT, as well as on broader family health outcomes.
Keywords: male involvement